Gender Bias in Justice Evaluations of Earnings: Evidence From Three Survey Experiments - Sauer, Carsten (Frontiers in Sociology, 2020)
Previous studies in sociological justice research found mixed results on the gender bias in justice evaluations of earnings. Some studies report a just gender pay gap favoring men; others do not find this gap. This study investigates the gender bias in justice evaluations by linking it to the inequality structure people are embedded in. The empirical analyses are based on three factorial survey studies that consist of fictitious full-time employees with varying characteristics including sex. One study was conducted with social sciences students and two with population samples of German inhabitants. Results show that social sciences students revealed no gender bias in their evaluations. In the population surveys, both men and women, showed a rating behavior favoring male employees. Respondents living in federal states with high actual gender pay gaps produced a larger bias favoring men. The findings indicate that actual inequalities between men and women influence the gender bias in justice evaluations.